Impact of ambient temperature on adverse pregnancy outcomes: a birth cohort study in Fuzhou, China - Lin, Jinfeng; Yang, Yan; Nuermaimaiti, Ayinasaer; Ye, Tingting; Liu, Jingwen; Zhang, Zitong; Chen, Yifeng; Li, Qingyu; Wu, Chuancheng; Liu, Baoying; Xu, Rongxian; Xia, Yong; et al. (Frontiers in Public Health, 2023)
Background Previous studies have identified a series of specific adverse pregnancy outcomes (APOs) linked with temperature extremes. Most of them focus on preterm birth, low birth weight, and stillbirth. Other possible adverse outcomes were under-researched. This study aimed to investigate the impact of ambient temperature on maternal complications, white blood cell count (WBC), newborn hearing, and neonatal jaundice. Methods A total of 418 participants were recruited from Fuzhou Maternity & Child Healthcare Hospital in 2016. Participants were invited to fill out a structured questionnaire. The gridded near-surface air temperatures at a resolution of 0.1°* 0.1° for Fuzhou were extracted from a published dataset. Meteorological data and PM2.5 were extracted based on participants’ residential addresses using R packages “ncdf4” and “raster.” Multivariate logistic regression models were used to quantify the effects of ambient temperature on APOs after controlling for confounders. Results Overall, there were 107 APOs, accounting for 25.6% of all participants. Every 1°C increase in mean temperature was associated with a 10.0% increase in APOs (aOR = 1.100, 95%CI 1.006–1.203) during the period of early pregnancy. However, negative associations were observed in the middle pregnancy period, and a 1°C increase in mean temperature was associated 8.8% decrease in APOs (aOR = 0.912, 95%CI 0.846–0.982). Diurnal temperature variation had a significant impact on APOs in the third trimester. Infant jaundice was negatively associated with temperature exposure in the middle and late pregnancy periods. The risk of neonatal jaundice increased at lag weeks 2–9 in the first trimester, with the greatest lagged effect (aOR = 1.201, 95%CI 1.020–1.413) observed at lag week 3. A 1°C increase in mean temperature led to a 29.6% (aOR = 1.296, 95%CI 1.019–1.649) increase in high WBC. A 1°C increase in temperature variation was associated with more than two times (aOR = 2.469, 95%CI 1.001–6.089) increase of high WBC in the first trimester and about five times (aOR = 4.724, 95%CI 1.548–14.409) increase in the third trimester. Conclusion Ambient temperature affects neonatal jaundice, newborn hearing loss, and infections during pregnancy. In addition to the identified epidemiologic link and susceptible exposure windows, there is a need to understand the underlying biological mechanisms for better recommendations for climate change adaptation policies.